In silico Analysis of Gamma-Secretase-Complex Mutations in Hidradenitis Suppurativa Demonstrates Disease-Specific Substrate Recognition and Cleavage Alterations - John W. Frew; Kristina Navrazhina; Kristina Navrazhina (Frontiers in Medicine, 2019)
Background: Familial Hidradenitis Suppurativa and Familial Alzheimer's Disease are both associated with Gamma-Secretase Complex mutations; however, the two diseases are not epidemiologically associated. Understanding the molecular differences between the two diseases may aid in the development of hypotheses for differing pathogenesis and ultimately, targets for detection.Aims: To characterize the in silico structural and functional alterations to the Gamma Secretase Complex in documented mutations in Familial Hidradenitis Suppurativa, along with comparison of downstream substrate recognition and cleavage.Methods:In silico analysis of publicly available genomic data, assessment of protein structure and binding affinity using Swiss-model and Dynamut was undertaken. Differential Expression was expressed using Log Fold Change using the general framework for linear models in R. Differentially expressed genes (DEGs) were defined by FCH ≥1.5 or ≤−1.5 and false discovery rate (FDR ≤ 0.05).Results: Twenty three of 39 mutations in HS are degraded via nonsense mediated decay with altered substrate and binding affinity of substrates identified in the remaining mutations. Significant differential expression of ErbB4, SCNB1, and Tie1 in lesional skin was specific to Hidradenitis Suppurativa and EphB2, EPHB4, KCNE1, LRP6, MUSK, SDC3, Sortilin1 in blood specific to Familial Alzheimer's Disease.Discussion and Conclusions: We present the first in silico evidence as to the impact of documented mutations in Familial Hidradenitis Suppurativa. We also demonstrate unique substrate recognition and cleavage between Hidradenitis Suppurativa and Familial Alzheimer's Disease, providing a potential explanation as to why the two diseases do not occur within the same pedigree. These proteomic signatures may be a first step in identifying reliable biomarkers for Familial Hidradenitis Suppurativa.